2001
DOI: 10.1111/1467-8330.00193
|View full text |Cite
|
Sign up to set email alerts
|

NAFTA's Labor Side Agreement and International Labor Solidarity

Abstract: The North American Free Trade Agreement (NAFTA) and its supplemental labor pact, the North American Agreement on Labor Cooperation (NAALC) reflect the uneven advances of labor rights advocacy in connection with international trade. NAFTA provides extensive rights and protections for multinational firms and investors in such areas as intellectual property rights and investment guarantees. The NAALC only partially addresses labor rights and labor conditions, but within its limits it has shown itself to be a viab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 5 publications
0
19
0
Order By: Relevance
“…One well-documented consequence of the NAALC almost from its inception has been the facilitating role it has played in fostering transnational networking among unions and labour rights activists in the three countries (Compa;2001. This is in sharp contrast to the situation prior to the NAALC, where there was distance and even distrust between unions in the U.S. and in Mexico.…”
Section: B Studying Transnational Labour Advocacy Network In North mentioning
confidence: 99%
See 2 more Smart Citations
“…One well-documented consequence of the NAALC almost from its inception has been the facilitating role it has played in fostering transnational networking among unions and labour rights activists in the three countries (Compa;2001. This is in sharp contrast to the situation prior to the NAALC, where there was distance and even distrust between unions in the U.S. and in Mexico.…”
Section: B Studying Transnational Labour Advocacy Network In North mentioning
confidence: 99%
“…7 Articles and reports that document the earlier cases include Human Rights Watch, 2001, Compa, 2001, Schurtman, 2005, Graubart, 2005. Questions concerning the efficacy are raised by Delp et.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Trade unions are either excluded from these, or included with severely prescribed powers, and engaged in decision-making where they are not disposed to support the initial premise of the argument. Characteristic examples might be a comparison of the in fluence and power of an institution such as the International Labour Organization with that of the World Trade Organization; or the limited impact of trade union voice in the North American Free Trade Agreement (but see Compa, 2001, for some examples of solidarity action). A concomitant development has been the emergence of civil society organizations that replicate or replace trade union activity, and assume a representational function that has greater influence within global governmental organizations (see Eade and Leather, 2005, for a collection that discusses this relationship).…”
Section: Global Restructuringmentioning
confidence: 99%
“…Although much was made of the "race to the bottom" in the late 1990s, Latin Americanists have shown that institutional channels exist to protect labor's rights (Compa 2001;Kay 2005;Murillo and Schrank 2005).…”
Section: Tilly Globalization and Labor's Rightsmentioning
confidence: 99%